Ultra high voltage MOS controlled 4H-SiC power switching devices. (28th July 2015) - Ryu, S; Capell, C; Van Brunt, E; Jonas, C; O'Loughlin, M; Clayton, J; Lam, K; Pala, V; Hull, B; Lemma, Y; Lichtenwalner, D; Zhang, Q J; et al.
Abstract: Ultra high voltage (UHV, >15 kV) 4H-silicon carbide (SiC) power devices have the potential to significantly improve the system performance, reliability, and cost of energy conversion systems by providing reduced part count, simplified circuit topology, and reduced switching losses. In this paper, we compare the two MOS based UHV 4H-SiC power switching devices; 15 kV 4H-SiC MOSFETs and 15 kV 4H-SiC n-IGBTs. The 15 kV 4H-SiC MOSFET shows a specific on-resistance of 204 m Ω cm 2 at 25 °C, which increased to 570 m Ω cm 2 at 150 °C. The 15 kV 4H-SiC MOSFET provides low, temperature-independent, switching losses which makes the device more attractive for applications that require higher switching frequencies. The 15 kV 4H-SiC n-IGBT shows a significantly lower forward voltage drop ( V F ), along with reasonable switching performance, which make it a very attractive device for high voltage applications with lower switching frequency requirements. An electrothermal analysis showed that the 15 kV 4H-SiC n-IGBT outperforms the 15 kV 4H-SiC MOSFET for applications with switching frequencies of less than 5 kHz. It was also shown that the use of a carrier storage layer (CSL) can significantly improve the conduction performance of the 15 kV 4H-SiC n-IGBTs.